2020
DOI: 10.3390/vetsci7020047
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Multibacterial Granulomatous Myositis in a Horse: First Report in Italy

Abstract: Infectious causes of myositis are reported relatively uncommonly in horses. Among them, bacterial causes include Streptococcus equi subsp. zooepidemicus, Actinobacillus equuli, Fusobacterium spp. Staphylococcus spp, and Corynebacterium pseudotuberculosis. Infection can be spread to muscles via haematogenous or extension from skin lesions. Parasitic myositis has also been documented. In this report, a 12 year-old Italian Quarter Horse mare presented with diffuse subcutaneous nodules and masses ranging from 2 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
1
0
2
Order By: Relevance
“…The absence of genotype patterns associated with hosts and biovars may have been related to the low representative sampling for these categories, since 4 of the 78 strains of C. pseudotuberculosis belonged to biovar Equi, and most isolates were from goats. Recently it has been observed that the C. pseudotuberculosis biovar Equi can also infect small ruminants (DoMENIS et al, 2018) and the biovar ovis has previously been isolated from horses (RIFICI et al, 2020), showing that there is no host specificity regarding the different C. pseudotuberculosis biovars.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of genotype patterns associated with hosts and biovars may have been related to the low representative sampling for these categories, since 4 of the 78 strains of C. pseudotuberculosis belonged to biovar Equi, and most isolates were from goats. Recently it has been observed that the C. pseudotuberculosis biovar Equi can also infect small ruminants (DoMENIS et al, 2018) and the biovar ovis has previously been isolated from horses (RIFICI et al, 2020), showing that there is no host specificity regarding the different C. pseudotuberculosis biovars.…”
Section: Discussionmentioning
confidence: 99%
“…As colônias obtidas no ágar chocolate tiveram identificação realizada em equipamento Biotyper (Bruker Daltonics, Billerica, MA), baseado em MALDI TOF MS. Após cultivo em ágar BHI (infusão de cérebro e coração) por 24 horas a 37°C, uma colônia isolada foi aplicada em um poço da placa de aço alvo MALDI Biotyper. Adicionou--se ao poço 1 μl de ácido fórmico (70%) e 1 μl de matriz MALDI-TOF MS (composta por uma solução saturada de ácido α-ciano-4-hidroxicinâmico), deixando-se secar em temperatura ambiente (ASSIS et al, 2017;RIFICI et al, 2020).…”
Section: Identificação Do Microrganismo Por Maldi Tofunclassified
“…Antes que as medições da amostra fossem registradas, o espectrômetro foi calibrado usando-se um padrão de teste bacteriano (E. coli DH5 alfa). Pontuações de corte recomendadas pelo fabricante foram usadas para identificação, com pontuações ≥2.000, indicando identificação em nível de espécie, enquanto pontuações ≥1,700 e <2.000 indicam identificação em nível de gênero e pontuações <1.700 não indicam uma identificação confiável (ASSIS et al, 2017;RIFICI et al, 2020).…”
Section: Identificação Do Microrganismo Por Maldi Tofunclassified